Fuzzy logic method for making push notifications on monitoring system of IoT-based electric truck charging - Al Madani Kurniawan, Aqsha; Khaula Amifia, Lora; Iskandar Riansyah, Moch.; Furizal, Furizal; Suwarno, Iswanto; Ma’arif, Alfian; Maghfiroh, Hari (Bulletin of Electrical Engineering and Informatics, 2025)
To minimize the negligence when charging electric vehicles, it is deemed important to have an internet of things (IoT) based monitoring system using a notification feature. The monitoring system of electric vehicle battery charging used a voltage divider and temperature sensor (DS18B20) installed on the Arduino Mega 2560 microcontroller with the addition of an ESP8266 Wi-Fi module for sending microcontroller data into the Blynk platform. A notification feature was added as the reminder that the battery has been overcharging or overheating. This study applied the Mamdani fuzzy logic method to determine the conditions when notifications must appear. The results of the application of the Mamdani fuzzy logic method were able to determine the conditions for push notifications to appear using the parameters as desired; by so doing, it is possible to create a battery monitoring system with accurate push notification feature to prevent the battery from being overcharged and overheated.